Supporting the Waldensians: The Politics of Transnational Aid in the Dutch Republic, 1655-1731 - Boersma, Erica (Early Modern Low Countries, 2022)
Early modern aid to foreign fellow believers is usually seen as an expression of confessional solidarity, initiated by and through religious networks. By studying four collections organised in the Dutch Republic between 1655 and 1731 in aid of Waldensians persecuted in Savoy, this article argues for a broadening of our perspective on transnational aid beyond the narrow confines of religious solidarity. It investigates the role of the Dutch civil authorities in the provision of transnational aid to foreign Protestants, through an analysis of the decision-making process that followed aid requests, the manner in which charitable collections were organised, and how the resulting proceeds were used. Even if aid was only given to fellow believers, for the Dutch authorities such aid was never merely a question of confessional solidarity: it was first and foremost an instrument of national foreign policy. This adds an important dimension to our understanding of transnational aid to foreign fellow believers.